Investigation Diarrhea Cases in Child in Palembang City 2015-2016 With Geographic Information System Approach - Amrina Rosyada; Dini Arista putri; Nur Alam Fajar (Faculty of Public Health, Andalas University, 2018)
Diarrhea cases in children under five are still one of the causes of the death of most children. Based on reports from the Palembang City Health Office, there is an increase in the number of diarrhea cases in urban areas between 2015-2016. There is one health center in urban areas that has a 4-fold increase between 2015-2016. The purpose of this study was to investigate the causes of an increase in diarrhea cases in the working area of Punti Kayu health center which included urban areas. This research is a qualitative descriptive study using secon-dary data, interviews with 3 health center staff and regional observations. The research was conducted in the working area of Punti Kayu Palembang Health Center. The results will be analyzed using the GIS approach to produce a map of the spatial distribution of diarrhea cases in children between 2015-2016 in the city of Palembang. In addition, the Content Analysis method to investigate the causes of increased cases. After analysis, it was found that between 2015-2016 the highest increase in cases was in Alang-alang sub-district where there was the Punti Kayu Health Center. The cause of the increase in the number of cases is due to the presence of non-working areas in Punti Kayu health centers such as Sukarame, Talang Kelapa, and Social along with the widespread use of National Health Insurance. In addition, health promotion to the homes of most residents was rejected. The need for innovation in raising awareness about the importance of private sanitation and the need for separation of reporting between patients in the work area and non working areas so that it is clear how many cases in the area need to be intervened by the health care